Designer genes: fashioning mission purposed microbes - Abdul Rahim, Raha (Universiti Putra Malaysia Press, 2010)

(untitled)
Genes are pieces of DNA that give mankind their genetic heritage. They are passed down through generations of living organisms copiously and diligently by mechanisms that have still not been fully deciphered. These genes are very stable and any changes will either be repaired or will cause malady to the cells. However, natural, `quirky’ things do happen and changes to the genes that are beneficial to the host cells will be well accepted and embraced as part of life’s progression. Nevertheless, it is now the beginning of the era of direct genetic modification. Whilst images of `Terminators’ and `Transformers’ would initially come to mind when the word `artificial intelligence’ is mentioned, the first such `artificial being’ is actually a simple single celled microorganism. In the area of biotechnology, microbes are usually used as the source of useful proteins, enzymes, metabolites and antibiotics. The first altered organisms emerged from recombinant DNA technology in the mid-70s. Microorganisms such as Escherichia coli, Saccharomyces cereviciae and Bacillus subtilis have been genetically modified and used to produce industrially and pharmaceutically important proteins and enzymes. More recently, several types of microbes including Salmonella spp, Lactobacillus spp and Lactococcus spp were characterized and are identified as potential vaccine carriers and producers. Whilst there are many success stories, the development of better systems and microbial hosts for the improved production of important biotechnology products is still being relentlessly pursued. This publication contains examples of work carried out by our research group in the design and development of gene carriers and microbes aimed at advancing the production of homologous and heterologous proteins. It is hoped that the work described here will provide insights into the multiple approaches needed in the development of mission purposed bacterial strains, specifically L. lactis, for use in the diverse areas of biotechnology. The identification of new plasmids and specific characterisation of cryptic lactococcal plasmids are presented, and the construction of new and useful plasmids is discussed. In addition, the development of new strains of microbes harbouring useful proteins is described